RANCANG BANGUN APLIKASI GAME PUZZLE BERBASIS ANDROID MENGGUNAKAN ALGORITMA DECISION TREE - Muhaimin Hasanudin; Turki Salim; Arkan Nur Robby (UNIVERSITAS RAHARJA, 2017)
The development of games today is very rapid and has become part of the lifestyle. A puzzle game is an application that can be used to hone thinking and memory skills where users have to find a way out and collect special items that have been provided at every level of the game . The player must collect all the white orb in each level to get the key to move to the next level but the player will be confronted by the constraints on how to find the key and retrieve it . The game is designed using decision tree and game algorithms designed using Game Maker Studio that is applied to Android devices.